A Critical Review of Lion Research in South Africa: The Impact of Researcher Perspective, Research Mode, and Power Structures on Outcome Bias and Implementation Gaps - Sobratee, Nafiisa; Slotow, Rob (Frontiers in Ecology and Evolution, 2019)
Understanding the state of research, and its effectiveness, in a predominantly Life Sciences sphere requires an assessment of knowledge growth dynamics, and the associated scientific and bibliometric impacts. We aim to create and evaluate, in a systematic review process, a macro-structure of the science generated in lion research in South Africa (SA) from 1990 to 2018. First, we classified the evidence architecture of lion research data extracted from the Web of Science Core Collection. Then, we identified prominent features that the datasets reveal in terms of authorship and ownership, as defined by first author affiliation, geographical location. Fifteen sub-disciplines were identified to characterize the topics. From 2000 onwards, multidisciplinary and interdisciplinary contributions started to emerge, catering for research problems defined at the interface of the academic-practitioner domains. These included social and economics components, and were aligned with conservation framings that seek to evaluate conservation within market-based versus people-based approaches. Study areas were concentrated within SA (61.8%) and the remainder was either conducted in the rest of Africa (22.9%), or in various combinations of geographical focus. Author affiliation indicated that 63.1 % of first authors had a South African affiliation. The rest of Africa was poorly represented at 2.4%. The majority (57.1%) of the first authors was male, but from 2014 to 2018, female researchers outnumbered males; however, male first authors continued to be cited more frequently. Furthermore, we provide a systemic analysis of the way in which research contributes to lion conservation. Overall, three voices dominate this area. Firstly, Mode 1 research has been driving research output in a ‘vicious circle’, motivated by researchers’ quest for accumulating academic rewards. Secondly, the citation impact shows a gender disparity against the recognition of female researchers. Lastly, a power imbalance against authors from the rest of Africa became apparent, whereby their role is mainly shaped towards being team contributors. This research shows that effective conservation requires appropriate knowledge to be generated, and this to be effectively translated into practical applications, with all perspectives providing the opportunity for balanced contribution and influence. Imbalances such as revealed are here likely to prevail more broadly.